Updates in insomnia diagnosis and treatment. (September 2019) - Bragg, Scott; Benich, JJ; Christian, Natalie; Visserman, Josh; Freedy, John
Introduction: Insomnia is the most commonly reported sleep disorder and remains undertreated in many patients. New changes to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, have changed the way insomnia is diagnosed. In patients who suffer from insomnia, a number of available treatment options exist including both behavioral therapy and medications. Literature Review: First line therapy for insomnia should always include behavioral modifications such as sleep hygiene and insomnia-oriented cognitive behavioral therapy. In patients deemed to need pharmacotherapy, first line medications include nonbenzodiazepine hypnotics (i.e., z-drugs) and antidepressants depending on the patients' needs and comorbidities. The risk of next day impairment, parasomnias, and central nervous system depression are some of the most feared side effects with z-drugs. Second line drug therapy includes melatonin and suvorexant. Several concerns exist for suvorexant similar to other insomnia medications, but melatonin remains one of the safest medication alternatives. Other medication options such as benzodiazepines, antihistamines, and antipsychotics should rarely be used because of weak effectiveness data or serious safety concerns. Discussion: The most appropriate treatment plan needs to be tailored to meet the needs of individual patients. Many patient factors (e.g., age, other comorbidities, specific problems with sleep) need to be considered before prescribing drug therapy for patients suffering from insomnia. Medications with the best evidence and fewest safety concerns should be prioritized when clinicians work with patients to determine the most appropriate treatment plan. Conclusions: Nondrug treatment should be the emphasis for managing insomnia, but several options exist for patients needing multimodal therapy to improve their symptoms and maximize their quality of life. Z-drugs and antidepressants are first line medications options, but other options may be considered when tailored to individual patients. Medications should only be used intermittently and short term until nondrug treatments help to change a patient's sleep routine.